Atypical use of pediatric flexible nails in the treatment of diaphyseal fractures in adults - Alessio, Pedrazzini (Acta Biomed, 2019)
BACKGROUND AND AIM OF THE WORK: Elastic intramedullary nails are commonly used for the treatment of diaphyseal fractures in adolescents and children. The major advantages are the minimally invasive nature of the technique, the short operation time, and the preservation of the growth plate and periosteum thus allowing bone healing within a closed and intact biological environment. Elastic nails are rarely applied to the adult fractures. METHODS: Five selected adult patients affected by diaphyseal fractures were treated using paediatric flexible nails T2 Kids (Stryker®, Mahwah, NJ, USA) as consequence of their poor clinical conditions, high risk of neurovascular injuries and skin/soft tissues problems. All patients were monthly clinically and radiographically evaluated after surgery until fracture healing. RESULTS: Radiological and clinical outcomes were satisfying. All fractures healed after a mean period of 3 months. No losses of reduction as well as mobilization/breakage of implant were observed. Conclusions: Use of pediatric elastic nails is a valid surgical option in treatment of diaphyseal fractures in selected adult patients who request fast and minimally invasive surgery as consequence of precarious clinical or soft tissues conditions. (www.actabiomedica.it)